Cannibalism mitigation in striped murrel, Channa striata, with hatchery seed weaned on pellet diet: A review. (23rd December 2021) - Raizada, Sudhir; Rawat, Anurag; Srivastava, Prem P.; Lal, Kuldeep K.
Abstract: Striped snakehead is one of the important food fish of high commercial value due to preference for its meat quality, therapeutic and antinociceptive properties. The species is distributed in many countries in South Asia to South‐East Asia. The current production of the species is largely contributed from the capture fisheries as there are several inherent problems associated with its farming. The major bottlenecks for aquaculture production are insufficient knowledge on reproductive biology, captive breeding, higher mortalities of larvae in nursing phases, intracohort cannibalism and non‐acceptance of artificial diet. The available information on these issues is sparse, often anecdotal and needs comprehensive up‐scaling. To address this gap, this review compiles the available information on this species to have a better understanding of reproductive biology, captive spawning, larval rearing, cannibalism mitigation, nursery rearing of seed in different rearing systems, and most important being weaning seed on the artificial diet so that this species could be cultured on artificial diets in the grow‐out systems. It is expected that this review would provide useful information for the production of feed‐weaned hatchery‐seed.